2004
DOI: 10.1111/j.1365-2621.2004.tb17857.x
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Lipid Fraction Quality of Margarine

Abstract: We studied 26 margarines, 13 from hydrogenated fats and 13 from fractionated or interesterified fats, by using (1) traditional routine analyses, (2) silica gel column chromatography to separate the polar compounds, (3) high-performance size-exclusion chromatography for the qualitative and quantitative determination of the single classes of substances constituting the polar compounds, and (4) gas chromatography to determine the fatty acid composition and the trans isomers. The margarines prepared from hydrogena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 16 publications
0
11
0
1
Order By: Relevance
“…The HPSEC analysis of PC has been successfully carried out to assess the actual oxidative and hydrolytic degradation of refined oils (including those used in high temperature processes) (Dobarganes and others 1988; Hopia 1993; Gomes and Caponio 1998). This technique was also adopted to monitor changes occurring during frying operations (Arroyo and others 1992; Garrido‐Polonio and others 1994) and to assess the quality of the lipid fraction of foods (Caponio and Gomes 2004; Caponio and others 2007; Summo and others 2008). …”
Section: Resultsmentioning
confidence: 99%
“…The HPSEC analysis of PC has been successfully carried out to assess the actual oxidative and hydrolytic degradation of refined oils (including those used in high temperature processes) (Dobarganes and others 1988; Hopia 1993; Gomes and Caponio 1998). This technique was also adopted to monitor changes occurring during frying operations (Arroyo and others 1992; Garrido‐Polonio and others 1994) and to assess the quality of the lipid fraction of foods (Caponio and Gomes 2004; Caponio and others 2007; Summo and others 2008). …”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that routine analytical determinations (free fatty acids, peroxide value, spectrophotometric constants) do not enable a good evaluation of the level of oxidative and hydrolytic degradation of refined vegetable oils and hydrogenated vegetable fats 17, 18. On the contrary, the HPSEC analysis of polar compounds is able to fully characterise the quality of the lipid fraction of foodstuffs.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it was used also to monitor the changes occurring in oil during frying (Arroyo, Cuesta, GarridoPolonio, López-Varela, & Sánchez-Muñiz, 1992; Garrido-Polonio, Sánchez-Muñiz, Arroyo, & Cuesta, 1994;López-Varela, Sánchez-Muñiz, Garrido-Polonio, Arroyo, & Cuesta, 1995) as well as to assess the quality of the lipid fraction of various foods (Caponio & Gomes, 2004;Caponio, Gomes, & Summo, 2003;Caponio, Gomes, Pasqualone, & Summo, 2007;Summo, Bilancia, & Caponio, 2008). It is worth noting that the products of triacylglycerol oxidation, at high amounts, could have harmful effects on the consumer's health (Billek, 2000;Saguy & Dana, 2003), as well as a pro-oxidative activity (Frankel, Neff, Selke, & Brooks,1988;Gomes, Delcuratolo, & Paradiso, 2008;Mistry & Min, 1988), that could negatively influence the shelflife of oils.…”
Section: Introductionmentioning
confidence: 99%